TUBERCULOSIS ABDOMEN: A REVIEW OF IMAGING FEATURES ON COMPUTED TOMOGRAPHY SCAN - Hafeez, Rabia; Inayatullah Memon,; Rubina Hafeez, (Journal of Postgraduate Medical Institute, 2022)
Objective: To evaluate the various imaging patterns of involvement of tuberculosis on CT scan abdomen. Methodology: In this study, Computed Tomography scans abdomen of 25 patients with abdominal tuberculosis were retrospectively reviewed to determine the spectrum and involvement of tuberculosis in the abdomen. The study was conducted at the Radiology department of, Ghulam Muhammad Mahar Medical college hospital, Sukkur, Sindh Pakistan between Jan-Jun 2021. Results: Lymphadenopathy was the most common feature in the CT scan study and was present in 20 (80%) cases involving mesenteric lymph nodes. Peripheral enhancing lymph nodes with central necrosis were the most common pattern of involvement in 10 (40%) cases. Peritoneal involvement was the second most common finding in 17 (68%) cases with ascites (wet peritonitis) seen in 11 (44%) and only ascites in 3 (12%) cases. Dry peritonitis (without ascites) was seen in 3 (12%) cases. Other findings included gastrointestinal involvement in 12 (48%) cases with the illeocecal region being the commonest site of involvement in 8 (66%) cases. The liver and spleen were the solid organ involvement in 3 (12%) cases. Conclusion: Our study demonstrates the various imaging manifestations of abdominal tuberculosis on CT scans. It can be considered as a diagnostic tool in the diagnosis of TB abdomen along with clinical and laboratory data.